2018
DOI: 10.1016/j.celrep.2018.10.080
|View full text |Cite
|
Sign up to set email alerts
|

A Metabolic Checkpoint for the Yeast-to-Hyphae Developmental Switch Regulated by Endogenous Nitric Oxide Signaling

Abstract: The yeast Candida albicans colonizes several sites in the human body and responds to metabolic signals in commensal and pathogenic states. The yeast-tohyphae transition correlates with virulence, but how metabolic status is integrated with this transition is incompletely understood. We used the putative mitochondrial fission inhibitor mdivi-1 to probe the crosstalk between hyphal signaling and metabolism. Mdivi-1 repressed C. albicans hyphal morphogenesis, but the mechanism was independent of its presumed targ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 73 publications
(105 reference statements)
0
53
1
Order By: Relevance
“…Previous studies in several fungal species have revealed roles for NO in global control of transcriptional and metabolic reprogramming and in modulating fungal morphogenesis and secondary metabolism 4548 . To test if NO is involved in transcriptional regulation in Fg during the pre-contact stage, the NO inducibility of NR as well as several other pre-contact DEGs was analyzed in Fg by RT-qPCR after the application of the NO chemical donor S-Nitroso-N-acetyl-DL-penicillamine (SNAP).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies in several fungal species have revealed roles for NO in global control of transcriptional and metabolic reprogramming and in modulating fungal morphogenesis and secondary metabolism 4548 . To test if NO is involved in transcriptional regulation in Fg during the pre-contact stage, the NO inducibility of NR as well as several other pre-contact DEGs was analyzed in Fg by RT-qPCR after the application of the NO chemical donor S-Nitroso-N-acetyl-DL-penicillamine (SNAP).…”
Section: Resultsmentioning
confidence: 99%
“…NO can also serve as a key messenger and a signaling molecule favoring fitness of both fungal partner and plant hosts during pathogenic as well as mutualistic interactions 40,5257 . Consequently, NO would deliver key messages from environmental signals and mediate the pathogen cellular responses through transcriptional reprogramming to facilitate lifestyle transition and niche adaptation 4548 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intracellular levels of NO was measured by flow cytometry adapted from previous method 62 . In brief, M. sympodialis WT and yhb1 Δ mutant were grown ON in mDixon media, washed once with PBS, and then incubated in PBS with agitation overnight.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, mutant strains or chemical interventions in glycolysis (Rodaki et al, 2006;Laurian et al, 2019) or fatty acid biosynthesis (Xu et al, 2009) showed defective growth, suggesting that these metabolic pathways can be important targets. Other therapeutic options that target C. albicans metabolism is to trigger endogenous nitric oxide (NO) production using compounds such as mdivi-1, which represses hyphal growth and the yeast-to-hypha transition and promotes metabolic reprogramming in the fungus (Koch et al, 2018). During growth and morphogenesis, C. albicans relies on OxPhos to produce ATP and therefore, mitochondria can be targeted for new antifungal drugs (Duvenage et al, 2019a).…”
Section: Role Of Cell Metabolism During Host-c Albicans Interactionsmentioning
confidence: 99%